The (In)significance of Executive Functions for the Trait of Self-Control: A Psychometric Study - Nęcka, Edward; Gruszka, Aleksandra; Orzechowski, Jarosław; Nowak, Michał; Wójcik, Natalia (Frontiers in Psychology, 2018)
Self-control is an individual trait defined as the ability to pursue long-distance goals in spite of the obstacles generated by current desires, innate or learned automatisms, and physiological needs of an organism. This trait is relatively stable across the life span and it predicts such important features as level of income, quality of social relationships, and proneness to addictions. It is widely believed that the cognitive substrate of self-control involves the executive functions, such as inhibitory control, shifting of attention, and working memory updating. However, the empirical evidence concerning the relationships between trait self-control and executive functions is not convincing. The present study aims to address two questions: (1) what is the strength of relationships between trait self-control and executive functions, and (2) which aspects of self-control are predicted by particular executive functions, if at all. In order to answer these questions, we carried out a psychometric study with 296 participants (133 men and 163 women, mean age 23.31, SD 3.64), whom we investigated with three types of tools: (1) a battery self-control scales and inventories, (2) a battery of executive functions tasks, and (3) two general intelligence tests. Structural equation modeling approach was used to analyze the data. We found that the latent variables representing self-control and the latent variable representing executive functions did not show any relationship. The standardized path coefficient between executive functions and general intelligence turned out rather strong. We conclude that the trait of self-control, measured with questionnaires, does not depend on the strength of cognitive control, measured with executive functions tasks.